The Oxford history of Anglicanism, volume IV : global Western Anglicanism, c.1910-present - Morris, Jeremy, ed. (Oxford : Oxford University Press, 2017)
This volume covers the twentieth-century history of Anglicanism in North America, Britain and Ireland, and Australasia. A historiographical introduction sets the scene in terms of currents of changing historical interpretation, highlighting particular perspectives on secularization, decolonization, mission, and the theological identity of Anglicanism which thread through the whole volume.
Anglicanism in Britain and Ireland/ Jeremy Morris
Includes bibliographical references and index.
Keywords: Anglican Communion -- History -- 20th century; Anglican Communion -- History -- 21st century